Liquid-filling auxiliary device for liquid-filled rock joints and its application. Issue 4 (October 2020) - Huang, J; Song, D Q; Liu, X L; Zhao, J; Wang, E Z; Wang, S J
Abstract: Filling joints are relatively common in rock mass-based geotechnical engineering. Presently, many researchers have concentrated on the analysis of filling joints with a solid or solid–liquid mixture as filling materials, while only few scholars have been investigating the filling conditions of liquid. In this study, a liquid-filling auxiliary device was developed. The primary test flow on a typical sample and its application in dynamic response to filling liquid were introduced. Granite and plexiglass were selected as test samples to emulate the structure of liquid-filled jointed rock mass, and a split Hopkinson pressure bar was employed for dynamic testing of the structure. The test results reveal that during data collection, pressure response of the filling liquid suddenly rises, experiences multiple fluctuations, and then gradually stabilizes. With an increase in the initial thickness of the filling liquid, peak value of the liquid pressure change exhibited an increasing trend. Further, dynamic response characteristics of filling liquid in liquid-filled jointed rock mass were analyzed. The outcomes provide a reference for the experimental study on the interaction mechanism between the stress wave and jointed rock mass and liquid.